Repair of humeral fractures with pins in pigeons - Kilic, S; Timurkaan, N (Indian Veterinary Journal, 2004)
Studies on avian fracture repair process are few as compared with other animals (Alkan et al., 1992; West et al., 1996; Wimsatt et al., 2000). Avian wing fractures are repaired with external or internal fixation methods, depending on many factors including type and location of the fracture, the size and age of the animal and number of bones involved (De Young and Probst, 1993). For internal fixation, bone, stainless steel and poly-methyl methacrylate (PMMA) pins, bone and stainless steel plates and stainless steel wire have been advocated (MacCoy and Haschek, 1988; Yamazoe et al., 1994; Wander et al., 2000). This study investigated the value of PMMA and xenograft cortical bone (XCB) pins for intramedullary repair of pigeon humeral fractures and their re-flying capabilities.